2014
DOI: 10.1158/2159-8290.cd-13-0782
|View full text |Cite
|
Sign up to set email alerts
|

Human and Mouse VEGFA-Amplified Hepatocellular Carcinomas Are Highly Sensitive to Sorafenib Treatment

Abstract: Death rates from hepatocellular carcinoma (HCC) are steadily increasing, yet therapeutic options for advanced HCC are limited. We identify a subset of mouse and human HCCs harboring VEGFA genomic amplifi cation, displaying distinct biologic characteristics. Unlike common tumor amplifi cations, this one seems to work via heterotypic paracrine interactions; stromal VEGF receptors (VEGFR), responding to tumor VEGF-A, produce hepatocyte growth factor (HGF) that reciprocally affects tumor cells. VEGF-A inhibition r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
134
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 178 publications
(140 citation statements)
references
References 55 publications
4
134
1
1
Order By: Relevance
“…A study was published in Cancer Discovery since submission of this manuscript demonstrating that VEGF-A amplified HCC are highly sensitive to sorafenib treatment (51). The findings of this study are highly compatible with the findings of our study showing that sorafenib treatment is preferentially acting anti-angiogenic with a very rapid dropout of endothelial cells as early as 24 h after the initiation of treatment (Fig.…”
Section: Note Added In Proofsupporting
confidence: 91%
“…A study was published in Cancer Discovery since submission of this manuscript demonstrating that VEGF-A amplified HCC are highly sensitive to sorafenib treatment (51). The findings of this study are highly compatible with the findings of our study showing that sorafenib treatment is preferentially acting anti-angiogenic with a very rapid dropout of endothelial cells as early as 24 h after the initiation of treatment (Fig.…”
Section: Note Added In Proofsupporting
confidence: 91%
“…We also measured proliferative indices of treated tumors and found decreased proliferation only in the group harboring the VEGFA amplicon. 3 As predicted by our hypothesis, this was accompanied by downregulation of HGF in amplicon-positive treated tumors. To test whether VEGFA overexpression alone is sufficient to instigate this protumorigenic crosstalk, we transduced a human HCC cell line (Hep3B) with a lentiviral vector overexpressing VEGFA.…”
supporting
confidence: 77%
“…2 Among several amplifications and deletions, 3 we focused on a recurrent amplification in Chr17qB3 harboring the VEGFA gene for 2 main reasons: (1) A syntenic amplification (Chr6p21) was previously reported in several different human tumor types, including HCC; 4 (2) It was previously shown that VEGFA promotes hepatocyte proliferation through induction of hepatocyte growth factor (HGF) in the sinusoidal endothelium. 5 Validating the aCGH results, we found Chr17qB3 amplification in 14% of 93 Mdr2 ¡/¡ HCCs analyzed, close to the frequency of 7-10% reported previously in human HCC.…”
mentioning
confidence: 99%
“…Moreover, the biomarkers selected by our method include VEGFA (vascular endothelial growth factor A), which plays a key role in angiogenesis. Some research suggests hepatocellular carcinoma (HCC) patients with elevated levels of VEGFA are distinctly sensitive to sorafenib [43], and VEGFA can therefore be used as a biomarker for personalized treatment of HCC with sorafenib [44]. Our result implies that VEGFA may also play a critical role in NSCLC patients with sorafenib.…”
Section: Brief Biological Analyses Of the Selected Genesmentioning
confidence: 63%